Policy Failure Revisited: Conceptual Implications from the Chilean Case of Transantiago - Olavarria-Gambi, M (SAGE Publications Inc., 2020)
The article analyzes the ability of policy failure frameworks to characterize and explain the reform of Santiago’s public transport system. It focuses on the following questions: When a policy may be deemed a failure, what sources led to the failure, and what lesson may be drawn from the case? It suggests that these three questions must be addressed simultaneously to integrally understand a policy failure. The case proposes areas of further investigation to elaborate a conceptual framework for a better understanding of why a particular policy may fail. Information comes from 53 interviews, official documents, academic bibliography, and the media. © The Author(s) 2018.